Ensilage in kansas - Davies, David Thomas (My University, 1895)
Introduction: While the system of ensilage has been practiced for centuries, it is true nevertheless that many are ignorant of the terms that must be used in discussing it. Ensilage is the name for the process of preserving any succulent food in an air tight pit or silo. Silage is the term used to designate the [illegible] so treated and the silo is the receptacle.
Citation: Davies, David Thomas. Ensilage in kansas. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Ensilage; Succulent food; Silo; Theses; Manuscripts (documents)